Theo đề, ta có:
4a-2b+c=0 và a-c=5
=>5a-2b=5 và a-c=5
=>c=a-5; 2b=5a-5
=>c=a-5; b=2/5a-5/2
=>f(x)=ax^2+(2/5a-5/2)x+a-5
\(\dfrac{f\left(x\right)}{x-2}=\dfrac{ax^2+\left(\dfrac{2}{5}a-\dfrac{5}{2}\right)x+a-5}{x-2}\)
\(=\dfrac{ax^2-2ax+\left(\dfrac{2}{5}a-\dfrac{5}{2}+2a\right)x-2\left(\dfrac{12}{5}a-\dfrac{5}{2}\right)+\dfrac{24}{5}a-5+a-5}{x-2}\)
\(=ax+\left(\dfrac{12}{5}a-\dfrac{5}{2}\right)+\dfrac{\dfrac{29}{5}a-10}{x-2}\)
Vì f(x) chia hết cho x-2 nên 29/5a-10=0
=>a=50/29
=>c=-95/29; b=-105/58